2022
DOI: 10.1093/trstmh/trac046
|View full text |Cite
|
Sign up to set email alerts
|

Critically ill COVID-19 patients in northeast Brazil: mortality predictors during the first and second waves including SAPS 3

Abstract: Background The Simplified Acute Physiology Score (SAPS) 3 is a reliable score to predict mortality. This study aims to investigate the predictive values of SAPS 3 and other clinical parameters for death in critically ill coronavirus disease 2019 (COVID-19) patients. Methods This is a prospective study in a tertiary hospital for patients who required intensive care due to COVID-19 infection in northeast Brazil. Two distinct gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
3
1
1
Order By: Relevance
“…that patients with low predicted risk of death in reality have higher risk of dying than expected and vice versa in patients with high predicted risk of death. In contrast to a single-center study from Brazil, the present study found SAPS3 to have similar prognostic performance across waves of COVD-19 [ 25 ]. Despite different viral strains, different patient case mixes, pressure on ICU resources and evolving practice of care, SAPS3 performed equally well across the waves of COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…that patients with low predicted risk of death in reality have higher risk of dying than expected and vice versa in patients with high predicted risk of death. In contrast to a single-center study from Brazil, the present study found SAPS3 to have similar prognostic performance across waves of COVD-19 [ 25 ]. Despite different viral strains, different patient case mixes, pressure on ICU resources and evolving practice of care, SAPS3 performed equally well across the waves of COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients in the second wave were less likely to need vasopressors and RRT during their ICU stay than patients in the first wave, as noted in other studies [39,40,48]. These results support the finding that better clinical outcomes in the second wave could be associated with younger age and less severe disease at ICU admission.…”
Section: Plos Onesupporting
confidence: 87%
“…Some studies support the association between dialysis and elevated mortality [17, 18]. In addition, the correlation between elevated SAPS 3 and pulmonary and renal dysfunction in predicting mortality has been reported [19].…”
Section: Discussionmentioning
confidence: 95%